Circulating microRNA Signature Associated to Interstitial Lung Abnormalities in Respiratory Asymptomatic Subjects - Blanca Ortiz-Quintero; Ivette Buendía-Roldán; Eric Gustavo Ramírez-Salazar; Yalbi I Balderas-Martínez; Sandra Lizbeth Ramírez-Rodríguez; Karen Martínez-Espinosa; Moisés Selman (Cells, 2020)
Interstitial lung abnormalities (ILA) are observed in around 9% of older respiratory asymptomatic subjects, mainly smokers. Evidence suggests that ILA may precede the development of interstitial lung diseases and may evolve to progressive fibrosis. Identifying biomarkers of this subclinical status is relevant for early diagnosis and to predict outcome. We aimed to identify circulating microRNAs (miRNAs) associated to ILA in a cohort of respiratory asymptomatic subjects older than 60 years. We identified 81 subjects with ILA from our Lung-Aging Program in Mexico City (n = 826). We randomly selected 112 subjects without ILA (Ctrl) from the same cohort. Using polymerase chain reaction PCR-Array technology (24 ILA and 24 Ctrl, screening cohort) and reverse-transcriptase quantitative polymerase chain reaction (RT-qPCR) (57 ILA and 88 Ctr, independent validation cohort) we identified seven up-regulated miRNAs in serum of ILA compared to Ctrl (miR-193a-5p, p < 0.0001; miR-502-3p, p < 0.0001; miR-200c-3p, p = 0.003; miR-16-5p, p = 0.003; miR-21-5p, p = 0.002; miR-126-3p, p = 0.004 and miR-34a-5p, p < 0.005). Pathways regulated by these miRNAs include transforming growth factor beta (TGF-β), Wnt, mammalian target of rapamycin (mTOR), Insulin, mitogen-activated protein kinase (MAPK) signaling, and senescence. Receiver operator characteristic (ROC) curve analysis indicated that miR-193a-5p (area under the curve AUC: 0.75) and miR-502-3p (AUC 0.71) have acceptable diagnostic value. This is the first identification of circulating miRNAs associated to ILA in respiratory asymptomatic subjects, providing potential non-invasive biomarkers and molecular targets to better understand the pathogenic mechanisms associated to ILA.